(untitled) (Third Sector Social Economic Review, 2022)
In recent years, interest of researchers and practitioners has gradually increased to concept of corporate reputation, which has contributed significantly to competitive advantage of institutions. When literature is examined, it is seen that majority of researches focus on the financial performance of enterprises. Aim of this study is to determine relationship between corporate reputation and employees’ affective commitment, job satisfaction and turnover intention. Research sample consists of employees of accommodation establishments operating in Cappadocia region. Data were collected by questionnaire. In preparation of questionnaire, corporate reputation scale developed by Fombrun (1996), the turnover intention scale developed by Seashore, Lawler, Mirvis, and Cammann (1982), the affective commitment scale developed by Meyer and Allen (1991) and the job satisfaction scale developed by judge, Locke, Durham, and Kluger (1998) was used. Frequency, reliability, correlation and regression analyses were used in analysis of obtained data. As a result of analysis; between corporate reputation and job satisfaction is positive at 41.4%; between corporate reputation and affective commitment is positive at 40.9%; between corporate reputation and turnover intention is negative at 47.1% relationships was determined. As a result of regression analysis, it was determined that corporate reputation positively effects job satisfaction and affective commitment, and negatively effects turnover intention.